INOVASI PUSAT PENGELOLAAN PENGADUAN MASYARAKAT (P3M) DI PUSAT INFORMASI PUBLIK (PIP) BALAI KOTA SEMARANG - Divani, Nadia Ulfa; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Public service innovation is a thing that must be done by the Government to be able to fulfill public need for fast and easy public service. Semarang City Government builds 3 in 1 IT-based public services innovation that can be used free called Public Information Center (PIP). One of the three services that provided by PIP is Citizen Complaints Management Centre (P3M). P3M is a recipient of complaints and aspirations which is an innovation from Complaint Management Service Center (P5). This study uses descriptive qualitative. This research aims to determine the innovation process of P3M services along with its supporting and inhibiting factors. The result of this research are P3M service innovation process can be seen from three aspect. The three aspects are opportunity, adoption, and implementation. The entire process of P3M service innovation has been running well but there is still a lack of promotion and understanding about the role of P3M. Factors that supporting P3M are (1) the desire to create new things; (2) innovation development creativity; (3) the presence of responsible person; (4) availability of facilities and infrastructure; and (5) supporting environmental conditions. The inhibiting factors of P3M innovation are (1) administrative pressure; (2) no appreciation yet; and (3) inability to face challange Keywords: